The Role of Mental Toughness and Intrinsic Motivation on Athletes' Resilience During the Covid-19 Pandemic - Hermahayu Hermahayu (Urecol Journal. Part H: Social, Art, and Humanities, 2021)
The Covid-19 pandemic is a global problem that has disrupted and delayed several national and international sports competitions. Athletes face the direct psychological consequences of Covid-19 such as cancellation of competitions, loss of support, lack of training, loss of income, excessive vigilance and anxiety. Therefore, this study aims to examine the relationship between resilience, mental toughness, and intrinsic motivation in national competitive athletes in Central Java, Indonesia during the pandemic. A total of 225 athletes from 23 sports who have participated in various nationally standardized competitions were involved in this study. The results showed that resilience was positively related to mental toughness (r = 0.616) and also to intrinsic motivation (r = 0.466). Mental toughness and intrinsic motivation, significantly predict resilience (R2 = 0.393). The findings of this study contribute that developing a mental toughness mindset and strengthening athletes' intrinsic motivation can represent intervention targets for resilient adaptation programs in the face of an uncertain pandemic situation.